The Risk of Ventricular Dysrhythmia or Sudden Death in Patients Receiving Serotonin Reuptake Inhibitors With Methadone: A Population-Based Study - Antoniou, Tony; McCormack, Daniel; Tadrous, Mina; Juurlink, David N.; Gomes, Tara (Frontiers in Pharmacology, 2022)
Background Methadone is associated with ventricular dysrhythmias and sudden death. Serotonin reuptake inhibitors (SRIs) may increase the risk of these events either by inhibiting metabolism of methadone’s proarrhythmic (S)-enantiomer, additive QT interval prolongation, or both. We sought to determine whether certain SRIs were associated with a higher risk of methadone-related ventricular dysrhythmias or sudden death. Methods We conducted a nested case-control study of Ontario residents receiving methadone between April 1, 1996 and December 31, 2017. Cases, defined as patients who died of sudden cardiac death or were hospitalized with a ventricular dysrhythmia while on methadone, were matched with up to 4 controls who also received methadone on age, sex, calendar year, and a disease risk score. We determined the odds ratio (OR) and P-value functions for the association between methadone-related cardiotoxicity and treatment with SRIs known to inhibit metabolism of (S)-methadone (paroxetine, fluvoxamine, sertraline) or prolong the QTc interval (citalopram and escitalopram). Patients who were not treated with an SRI served as the reference group. Results During the study period, we identified 626 cases and 2299 matched controls. Following multivariable adjustment, we found that recent use of sertraline, fluvoxamine or paroxetine (adjusted OR 1.30; 95% confidence intervals [CI] 0.90 to 1.86) and citalopram and escitalopram (adjusted OR 1.26; 95% CI 0.97 to 1.63) were associated with small increases in the risk methadone-related cardiac toxicity, an assertion supported by the corresponding P-value functions. Interpretation Certain SRIs may be associated with a small increase in cardiac toxicity in methadone-treated patients.